Electrodeposition of Ni-nano composite coatings: a review. Issue 12 (2nd December 2018) - Raghavendra, Challakere Ramadas; Basavarajappa, Satyappa; Sogalad, Irappa
Abstract: Since the inception of Nickel electrodeposition coating by G. Bird in 1837, it has been the area under discussion of research. From the past several decades, prominence has shifted for its exclusive applications and properties in the field of engineering. It has several advantages as compared to conventional electrolyte coating. Due to excellent tribological properties the electroplated nickel coatings are widely used in chemical, automobile, aerospace, and electrical industries. To enhance these properties of electrodeposition of nickel coating the researchers have introduced second phase particles such as SiC, ZrO2, B4 C, TiO2, Al2 O3, Si3 N4, CeO2 etc. These researchers have shown that theses second phase particles will result in the improvement of tribological characteristics. Industries demand new coating materials with enhanced tribological characteristics for its applications. The present article review the tribological advantages of different electrodeposited nickel coatings based on the bath types and structure.